The Revolutionary War - Neimeyer, Charles Patrick, 1954- (Greenwood Press "Daily life through history" series. American soldiers' lives., 2007)
Nearly everyone in the U.S. has studied the Revolutionary War. Too often, however, historians of the Revolution focus on the activity of the army without noticing what was taking place inside the army. Making liberal use of diaries and correspondence by the soldiers and their families, Charles P. Neimeyer tells the stories of the men and women who fought for the young country's independence. Sometimes starting off as rag-tag groups of men shooting off their muskets at geese just for the thrill of the sound, the soldiers became more disciplined and focused. The army recruited a significant numb.